Designing consumer redress: a dispute system design (DSD) model for consumer-to-business disputes. (2nd January 2018) - Gill, Chris; Williams, Jane; Brennan, Carol; Hirst, Carolyn
Abstract : This paper proposes a model for designing consumer dispute resolution (CDR) mechanisms (including conciliation, adjudication, arbitration and ombuds schemes). This field has expanded significantly in recent years, replacing courts as the primary forum of dispute resolution in some areas of consumer-to-business activity. This expansion has been ad hoc, with a lack of consistency in the design of CDR mechanisms and in the overall shape of the CDR landscape. In light of the recent implementation of the EU's Directive on Consumer Alternative Dispute Resolution and Regulation on Consumer Online Dispute Resolution, Dispute System Design (DSD) requires urgent attention to ensure that the design of future mechanisms is based on coherent principles. A failure to address this issue risks undermining the legitimacy of state-sanctioned dispute resolution. The model described in this paper proposes a systematic approach and aims to: synthesise existing DSD models; apply the concepts of DSD to the field of CDR; and provide a framework that may be of use in other disputing contexts.